TRANSFORMASI DIGITAL UMKM MELALUI IMPLEMENTASI SISTEM INFORMASI AKUNTANSI: EVALUASI SISTEM IPOS 5.0 PADA UD ABC - Haripin; Diva Artha Meivia; Medina Haqi Pratiwi; Prita Aulia Oktaviani; Eny Ayu Wulandari; Marshanda Tasha Misvida; Yudha Febri Eka Wardana; Elsa Elsa; Siti Aisyah (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
Digital transformation has become an important strategy for MSMEs to improve operational efficiency and competitiveness, one of which is through the implementation of the iPOS 5.0 Accounting Information System (AIS). This study aims to evaluate the implementation of iPOS 5.0 at UD ABC in supporting transaction recording, financial reporting, and the effectiveness of internal controls. The study employed a descriptive qualitative method with a case study approach. Data were collected through interviews with the finance department, observations, and document reviews. The findings indicate that iPOS 5.0 is capable of integrating inventory, sales, purchasing, payment, and accounting processes more effectively and efficiently. The system also provides financial information that is faster, more accurate, and reliable, thereby facilitating managerial decision-making. However, several weaknesses remain, including manual transaction authorization, limited report customization, and the absence of formal policies regarding risk management and information security.